Crisis, What Crisis? The Media: Business and Journalism in Times of Crisis - Rosario de Mateo; Laura Bergés; Anna Garnatxe (tripleC: Communication, Capitalism & Critique)
The global financial and economic crisis is often used to justify a crisis of media and journalism: lower advertising, collapses in the share price, falls in consumption, more unemployment. But is this just a business crisis, or is it also a crisis in journalism and its role in democratic societies? In this case, is the journalism crisis attributable to the economic crisis or, rather, was it forged during the years of high profitability and high salaries in the mass media? These two sides of the crisis, in media industry and in journalism, are addressed in this article, which explores the evolution of mainly Spanish media in the years before the crisis. However, in order to understand how they reached the current situation, political and economic transformations in what has been called the Information Society and neoliberal globalization must be addressed.